Poder y favor en la corte virreinal del Perú: los criados del marqués de Montesclaros (1607-1615) - Latasa, Pilar (2012)
Spanish kings conferred on their viceroys in the Indies the prerogative of extending largesse to subjects. A distinction is often made between rewards accorded to those who merited recognition and to members of the viceroy’s entourage: servants, relatives, and close collaborators who had traveled with them. However, a case study of the Marquis of Montesclaros’ patronage during his administration in Peru reveals the nuances in this dichotomy, among other things, that nepotism involved marriage strategies intended to incorporate selected servants into the local elite.